Biofilms in orthopedic infections: a review of laboratory methods. Issue 4 (April 2017) - Dibartola, Alex C.; Swearingen, Matthew C.; Granger, Jeffrey F.; Stoodley, Paul; Dusane, Devendra H.
Abstract : Bacterial infection after hardware implantation in orthopedic surgery is a devastating issue as it often necessitates increased hospital costs and stays, multiple revision surgeries, and prolonged use of antibiotics. Because of the nature of hardware implantation into the body, these infections are commonly in the form of attached biofilms. The current literature on a range of methodologies to study clinically explanted infected orthopedic hardware, with potential biofilm, in the laboratory setting is limited. General methods include traditional and advanced culturing techniques, microscopy imaging techniques, and techniques that manipulate genetic material. The future of diagnostic techniques for infected implants, innovative hardware design, and treatment solutions for patients all depend on the successful evaluation and characterization of clinical samples in the laboratory setting. This review provides an overview of current methods to study biofilms associated with orthopedic infections and insight into future directions in the field.